2014
DOI: 10.1016/j.mad.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Short and long telomeres increase risk of amnestic mild cognitive impairment

Abstract: Peripheral blood telomere length has been associated with age-related conditions including Alzheimer’s disease (AD). This suggests that telomere length may identify subjects at increased risk of AD. Thus, we investigated the associations of peripheral blood telomere length with amnestic mild cognitive impairment (aMCI), a putative precursor of AD, among Mayo Clinic Study of Aging participants who were prospectively followed for incident aMCI. We matched 137 incident aMCI cases (mean age 81.1 years, [range 70.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 46 publications
4
41
0
Order By: Relevance
“…This pattern of associations, which we also observed for the interaction between BC and CRP in this study, suggests the existence of an activation threshold, which is typical in inflammatory responses, particularly if they—such as those elicited by traffic air pollution—are induced through the NF-κB pathway (Nam et al 2009). Of note, a previous study described an L-shaped association of TL with mild cognitive impairment; in particular, TL in the top quintile, but not in other quintiles, was associated with relative odds of both prevalent and incident mild cognitive impairment (Roberts et al 2014). Alternatively, our finding might reflect a saturation effect among individuals with shorter TL.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This pattern of associations, which we also observed for the interaction between BC and CRP in this study, suggests the existence of an activation threshold, which is typical in inflammatory responses, particularly if they—such as those elicited by traffic air pollution—are induced through the NF-κB pathway (Nam et al 2009). Of note, a previous study described an L-shaped association of TL with mild cognitive impairment; in particular, TL in the top quintile, but not in other quintiles, was associated with relative odds of both prevalent and incident mild cognitive impairment (Roberts et al 2014). Alternatively, our finding might reflect a saturation effect among individuals with shorter TL.…”
Section: Discussionmentioning
confidence: 93%
“…Telomere length (TL) has been shown to decrease non-linearly with age across different tissues, including blood leukocytes, in living organisms (Saretzki and Von Zglinicki 2002; Young 2010). Shorter leukocyte TL has been associated with age-related diseases, such as cardiovascular disease (Fyhrquist et al 2011), cancer (Artandi and DePinho 2010), and cognitive impairment (Roberts et al 2014), as well as with mortality (Svenson et al 2009), although one study reported opposing associations (Sanchez-Espiridion et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Conversely, there is evidence that over-elongated telomeres represent pathological cell function with decreased DNA repair and increased cancer risk [9], which has also been shown in human embryonic stem cells [10], while "normally" long telomeres are protective, including against DNA damage. With respect to Alzheimer's disease, there is also evidence suggesting an increased risk of mild cognitive impairment related to both short and long telomeres [11]. Additionally, hippocampal cells of Alzheimer's disease brains are shown to have longer telomeres compared to control samples [12].…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that both short and long telomeres increase risk of amnestic mild cognitive impairment (41). Furthermore, longer telomeres are often associated with an increased risk for different cancer types (42).…”
Section: Discussionmentioning
confidence: 99%